Active and passive controls of 3D nanofluid flow by a convectively heated nonlinear stretching surface. (3rd June 2019) - Hayat, Tasawar; Aziz, Arsalan; Muhammad, Taseer; Alsaedi, Ahmed
Abstract: This article presents magnetohydrodynamic three-dimensional flow of nanoliquid by a nonlinear stretchable surface with active and passive controls of nanoparticles. A bidirectional nonlinear stretching surface generates the flow. The convective condition of heat transfer is taken into consideration. Impacts of thermophoresis and Brownian diffusion are present. Fluid is electrically conducted subject to a uniform applied magnetic field. Zero normal flux condition is defined to impulse the particles away from the surface in combination with nonzero normal flux condition. Convergent series solutions for the nonlinear governing system are established. Graphs have been sketched in order to analyze how the temperature and concentration distributions are affected by distinct physical flow parameters. Surface drag coefficients and heat and mass transfer rates are also computed.